Effect of Irrigating Agitation after Root End Preparation on the Wall Cleaning and Bond Strength of Calcium Silicate Material in Retrograde Obturation - Valencia, Yahir Muñoz; Vertuan, Gislene Cristina; Alcalde, Murilo Priori; Vivan, Rodrigo Ricci; Reis Só, Marcus Vinícius; Duarte, Marco Antonio Hungaro (European Journal of Dentistry, 2021)
Objective This study aimed to evaluate the cleaning efficacy of irrigant activation with a new ultrasonic tip in root-end preparations and to determine its influence on the bond strength of calcium silicate-based material.Materials and Methods Maxillary canines were prepared and filled, and their root ends resected. Root-end cavities were ultrasonically prepared and randomly distributed into four groups according to the final irrigation protocols: G1 (ultrasonic irrigation [UI] + saline solution [SS]), G2 (syringe irrigation [SI] + SS), G3 (UI + ethylenediaminetetraacetic acid [EDTA]), and G4 (SI + EDTA). Cleaning efficacy analysis employed 72 specimens (n = 18) split longitudinally for imaging of the same areas by scanning electron microscopy (SEM). The percentage of dentinal tubules opened before and after irrigation was used as evaluation parameter. Push-out testing employed 40 specimens (n = 10) sectioned apical region perpendicularly, which slice was placed on a testing machine for the bond strength measurement and failure mode was assessed by SEM. The data were statistically analyzed (α ≤ 0.05).Results G3 (UI + EDTA) removed the smear layer more effectively, showed the best tubule opening (p < 0.05), and presented the highest mean bond strength values (p < 0.05). Failure modes were predominantly adhesive, except for the G3 (UI + EDTA) group, in which they were mainly mixed (80%).Conclusion The results of this study suggest that EDTA 17% agitation promoted better cleaning and smear layer removal, improving the push-out bond strength of calcium silicate material in retrograde obturation.
Keywords: smear layer; bond strength; root-end cavity; retrograde filling; scanning electron microscopy; push-out